Urgent surgical approach for comminuted mandible fracture and considerations regarding airway risk. Case report - Damaceno Fernandes, Vinicius Juliate; Sol, Izabella; Rodrigues, Cristóvão Marcondes de Castro; Almeida, Vinícius Lima de; Batista, Jonas Dantas; Silva, Cláudia Jordão (Journal of Health & Biological Sciences, 2021)
Introduction: Jaw fractures are one of the most common sites of maxillofacial injuries. The location of the jaw makes it very vulnerable to direct impacts. The purpose of treatment is to restore aesthetic function. Case Report: The purpose of this report is to present a case of comminuted mandible fracture in a young male patient, treated urgently due to the need for maintenance of the airways, where fracture osteosynthesis surgery was submitted. Conclusion: The initial assessment of these trauma patients should follow the Trauma Life Support protocol, and structural damage should be investigated. Introduction: Jaw fractures are one of the most common sites of maxillofacial injuries. The location of the jaw makes it very vulnerable to direct impacts. The purpose of treatment is to restore aesthetic function. Case Report: The purpose of this report is to present a case of comminuted mandible fracture in a young male patient, treated urgently due to the need for maintenance of the airways, where fracture osteosynthesis surgery was submitted. Conclusion: The initial assessment of these trauma patients should follow the Trauma Life Support protocol, and structural damage should be investigated.